2014
DOI: 10.2147/ijwh.s56388
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human papillomavirus immunoglobulin G antibodies among women presenting at the reproductive health clinic of a university teaching hospital in Nigeria

Abstract: BackgroundHuman papillomavirus (HPV) is the cause of 90%–95% of squamous cell cancers. Persistent infection with high-risk HPV can lead to development of precancerous lesions of the cervix in 5%–10% of infected women, and can progress to invasive cervical cancer 15–20 years later. This study was conducted to determine the seroprevalence of HPV immunoglobulin G (IgG) antibodies among women of reproductive age attending a reproductive health clinic at Ahmadu Bello University Teaching Hospital, Zaria, Nigeria.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
16
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
13
16
3
Order By: Relevance
“…Though, seroprevalence studies has their limitations, such studies, such as the present study, provide a useful tool to understand the dynamics of HPV infection, thereby providing a baseline assessment for the incorporation of HPV vaccination programs in the State of Qatar. In the present study, we found a lower seroprevalence of 4.5% for HPV-IgG antibodies in Arab women than globally [32,33]. This low seroprevalence supports lower intensity of HPV transmission in the Arab female population, possibly due to poorly connected and sparse sexual networks, a result of the more conservative sexual norms in this part of the world [28].…”
Section: Discussionsupporting
confidence: 69%
“…Though, seroprevalence studies has their limitations, such studies, such as the present study, provide a useful tool to understand the dynamics of HPV infection, thereby providing a baseline assessment for the incorporation of HPV vaccination programs in the State of Qatar. In the present study, we found a lower seroprevalence of 4.5% for HPV-IgG antibodies in Arab women than globally [32,33]. This low seroprevalence supports lower intensity of HPV transmission in the Arab female population, possibly due to poorly connected and sparse sexual networks, a result of the more conservative sexual norms in this part of the world [28].…”
Section: Discussionsupporting
confidence: 69%
“…The finding however contrasts that of [28] that reported higher prevalence in single women. This finding also, does not agree with that of [13] that reported a similar HPV prevalence in both the single and married women. The absence of HPV infection in the single women could be because most of them take protective measures (using barriers) when having sex with their partners due to their fear of getting pregnant or contracting sexually-transmitted diseases.…”
Section: Discussioncontrasting
confidence: 99%
“…The data suggesting important elements of such a lifestyle include latter age at first sexual intercourse, a limited number of pregnancy, and greater likelihood of undergoing cytological screening and reduce exposure to carcinogen in household environments. This observation is similar to those of [29,25,20,13] that reported highest prevalence in elementary educated women, there was a statistically significant association between HPV infection and education.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Aminu et al. 3 reported a seroprevalence of 42.9% for IgG antibodies to HPV among Nigerian women in the northern region. HPV infection rates ranged from 30.4% to 36.5% among female outpatients in southwest Nigeria.…”
mentioning
confidence: 99%